Actitudes protectoras relacionadas con la seguridad vial en conductores de Villavicencio (Colombia) (2021)
The aim of this paper was to know the protective road safety attitudes level in drivers from a Colombian city. According to this, a 18 item scale was used, measuring driving risk and safety behaviors, and emotions. Sample was non-randomized, with 1018 car, bus, motorcycle, taxi, van or trucks drivers. Results showed a high internal reliability of scale, and a factor structure with four dimensions. Also, male, people with low educational level or in union, and taxi and van/trucks drivers showed highest levels ofdriving risk attitudes and speeding. Anger level was higher for divorced people.